Closed-loop mechanical ventilation for lung injury: a novel physiological-feedback mode following the principles of the open lung concept. - Schwaiberger, David; Pickerodt, Philipp A.; Pomprapa, Anake; Tjarks, Onno; Kork, Felix; Boemke, Willehad; Francis, Roland C. E.; Leonhardt, Steffen; Lachmann, Burkhard (Journal of Clinical Monitoring & Computing, 2018)
Adherence to low tidal volume (VT) ventilation and selected positive end-expiratory pressures are low during mechanical ventilation for treatment of the acute respiratory distress syndrome. Using a pig model of severe lung injury, we tested the feasibility and physiological responses to a novel fully closed-loop mechanical ventilation algorithm based on the "open lung" concept. Lung injury was induced by surfactant washout in pigs (n = 8). Animals were ventilated following the principles of the "open lung approach" (OLA) using a fully closed-loop physiological feedback algorithm for mechanical ventilation. Standard gas exchange, respiratory- and hemodynamic parameters were measured. Electrical impedance tomography was used to quantify regional ventilation distribution during mechanical ventilation. Automatized mechanical ventilation provided strict adherence to low VT-ventilation for 6 h in severely lung injured pigs. Using the "open lung" approach, tidal volume delivery required low lung distending pressures, increased recruitment and ventilation of dorsal lung regions and improved arterial blood oxygenation. Physiological feedback closed-loop mechanical ventilation according to the principles of the open lung concept is feasible and provides low tidal volume ventilation without human intervention. Of importance, the "open lung approach"-ventilation improved gas exchange and reduced lung driving pressures by opening atelectasis and shifting of ventilation to dorsal lung regions.